2020
DOI: 10.21829/azm.2004.2022332
|View full text |Cite
|
Sign up to set email alerts
|

Nuevas especies y cambios taxonómicos para la herpetofauna de México

Abstract: Se hace una recopilación de los cambios taxonómicos y nomenclaturales que afectan la taxonomía de las especies mexicanas de anfibios y reptiles. Asimismo se da una lista de las especies nuevas para la ciencia descritas en los últimos once años y las especies que se citan por primera vez para México. Se registran estos cambios y adiciones hasta diciembre de 2003. Con esta información, se eleva el número de especies de anfibios y reptiles de México de 997 a 1165 desde la publicación de la última lista de especie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Publications such as Herpetology of Mexico ( Smith and Taylor 1966 ), and studies at the regional ( Pérez-Higareda and Smith 1991 ; Ramírez-Bautista 1994 ; Uribe-Peña et al 1999 ; among others), state ( Álvarez del Toro 1982 ; Vázquez-Díaz and Quintero-Díaz 1997 , 2005 ; Lemos-Espinal and Smith 2009 , 2016 ; Ramírez-Bautista et al 2009 , 2010 , 2014 ; Dixon and Lemos-Espinal 2010 ; Alvarado-Díaz et al 2013 ; Lemos-Espinal and Dixon 2013 ; Carbajal-Márquez and Quintero-Díaz 2016 ; Lemos-Espinal et al 2016 , 2017 , 2018a , b , 2019 ; Nevárez-de los Reyes et al 2016 ; Terán-Juárez et al 2016 ; Woolrich-Piña et al 2016 , 2017 ; Cruz-Sáenz et al 2017 ; González-Sánchez et al 2017 ; Palacios-Aguilar and Flores-Villela 2018 ; Ramírez-Bautista et al 2020 ; Rhodin et al 2021 ; Barragán-Vázquez et al 2022 ; Cruz-Elizalde et al 2022 ; Leyte-Manrique et al 2022 ; among others), and country levels ( Flores-Villela 1993a ; Flores-Villela and Canseco-Márquez 2004 ; Liner 2007 ; Wilson and Johnson 2010 ; Wilson et al 2013a , b ; Flores-Villela and García-Vázquez 2014 ; Parra-Olea et al 2014 ; Mata-Silva et al 2015 ; Johnson et al 2015 , 2017 ; Balderas-Valdivia and González-Hernández 2021 ; Mata-Silva et al 2021 ; Balderas-Valdivia et al 2022 ; Smith and Lemos-Espinal 2022 );…”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Publications such as Herpetology of Mexico ( Smith and Taylor 1966 ), and studies at the regional ( Pérez-Higareda and Smith 1991 ; Ramírez-Bautista 1994 ; Uribe-Peña et al 1999 ; among others), state ( Álvarez del Toro 1982 ; Vázquez-Díaz and Quintero-Díaz 1997 , 2005 ; Lemos-Espinal and Smith 2009 , 2016 ; Ramírez-Bautista et al 2009 , 2010 , 2014 ; Dixon and Lemos-Espinal 2010 ; Alvarado-Díaz et al 2013 ; Lemos-Espinal and Dixon 2013 ; Carbajal-Márquez and Quintero-Díaz 2016 ; Lemos-Espinal et al 2016 , 2017 , 2018a , b , 2019 ; Nevárez-de los Reyes et al 2016 ; Terán-Juárez et al 2016 ; Woolrich-Piña et al 2016 , 2017 ; Cruz-Sáenz et al 2017 ; González-Sánchez et al 2017 ; Palacios-Aguilar and Flores-Villela 2018 ; Ramírez-Bautista et al 2020 ; Rhodin et al 2021 ; Barragán-Vázquez et al 2022 ; Cruz-Elizalde et al 2022 ; Leyte-Manrique et al 2022 ; among others), and country levels ( Flores-Villela 1993a ; Flores-Villela and Canseco-Márquez 2004 ; Liner 2007 ; Wilson and Johnson 2010 ; Wilson et al 2013a , b ; Flores-Villela and García-Vázquez 2014 ; Parra-Olea et al 2014 ; Mata-Silva et al 2015 ; Johnson et al 2015 , 2017 ; Balderas-Valdivia and González-Hernández 2021 ; Mata-Silva et al 2021 ; Balderas-Valdivia et al 2022 ; Smith and Lemos-Espinal 2022 );…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Finally, between 1990 and 2000, a strong interest in biodiversity led to an assessment of the herpetofauna of Mexico at both the regional and state levels ( Flores-Villela and Canseco-Márquez 2004 ; Wilson et al 2013a , b ). Subsequently, information from these projects, along with long-term studies and continued sampling, provided a more accurate number of the species involved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also excluded from the most recent list of the herpetofauna of Chiapas, Mexico (Johnson et al 2015), the state that is closest to verified records of M. dorsalis in the neighboring country of Guatemala. No other publication on the herpetofauna of Mexico or Chiapas has indicated the presence of M. dorsalis in the country (Álvarez del Toro 1973Toro , 1983Flores-Villela 1993;Flores-Villela and Canseco-Márquez 2004;Köhler 2003Köhler , 2008Johnson et al 2010;Wilson and Johnson 2010;Luna-Reyes et al 2013). However, in an appendix of specimens examined, Montingelli et al (2019) listed a specimen that they identified as M. dorsalis from Chiapas, Mexico.…”
Section: Introductionmentioning
confidence: 99%